2021
DOI: 10.3390/jof7020075
|View full text |Cite
|
Sign up to set email alerts
|

The Host Immune Response to Scedosporium/Lomentospora

Abstract: Infections caused by the opportunistic pathogens Scedosporium/Lomentospora are on the rise. This causes problems in the clinic due to the difficulty in diagnosing and treating them. This review collates information published on immune response against these fungi, since an understanding of the mechanisms involved is of great interest in developing more effective strategies against them. Scedosporium/Lomentospora cell wall components, including peptidorhamnomannans (PRMs), α-glucans and glucosylceramides, are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 123 publications
0
13
0
Order By: Relevance
“…In a recent humoral study in mice by Buldain et al [61], Rbp1 from Lomentospora was shown for the first time to act as a fungal allergen. The allergic reaction occurred due to the recognition of immunoglobulin G (Ig-G) toward Rbp1 [62]. Despite the lack of evidence, Rhodotorula sp.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent humoral study in mice by Buldain et al [61], Rbp1 from Lomentospora was shown for the first time to act as a fungal allergen. The allergic reaction occurred due to the recognition of immunoglobulin G (Ig-G) toward Rbp1 [62]. Despite the lack of evidence, Rhodotorula sp.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva and serum from immunocompetent individuals were used in these studies [42,43]. Some of these antibodies produced by healthy populations may provide protection against fungal infections, and their antigenic targets may be investigated as therapeutic agents in the future [23] (Figure 1). these antibodies produced by healthy populations may provide protection against fungal infections, and their antigenic targets may be investigated as therapeutic agents in the future [23] (Figure 1).…”
Section: Pathogenesis and Host Defensementioning
confidence: 99%
“…Depending on the site of entry, the immunological response varies, and different cells are challenged to remove the conidia. Initially, the innate immune system recognizes molecular components in the fungal cell wall through pattern recognition receptors (PRRs) [ 23 ]. The PRRs induce the synthesis of pro-inflammatory cytokines, phagocytosis, and adaptive immunity mechanisms.…”
Section: Pathogenesis and Host Defensementioning
confidence: 99%
See 2 more Smart Citations